Asupan Zat Gizi Dan Tingkat Pendapatan Keluarga Terhadap Kejadian Stunting Pada Anak Usia 3-5 Tahun - Grace K.L. Langi; Vera T. Harikedua; Rudolf B. Purba; Janeke I. Pelanginang (Jurnal GIZIDO, 2019)
One of the main challenges currently facing the health sector in Indonesia is chronic child malnutrition. Although many health developments and advances have been made in Indonesia over the past few years, the problem of stunting remains significant. The results of Basic Health Research showed that the prevalence of stunting in Indonesia in 2013 was 37.2%. The results of the Nutrition Status Assessment (PSG), in the province of North Sulawesi, the prevalence of stunting according to the TB / U index in 2017 increased by 31.4%. For Kotamobagu City the prevalence of stunting is 38.1%. To determine the relationship of nutrient intake and the level of family income to the incidence of stunting in children aged 3-5 years in the work area of ​​Upai City Health Center, Kotamobagu. This study used a cross sectional design with a sample size of 41 people. Measurement of variables was obtained from interviews using a questionnaire, 24-hour recall, and height measurements using microtoise. The results of this study indicate there is a relationship between iron intake with stunting, whereas energy intake has no relationship with stunting, protein intake has no relationship with stunting events, vitamin A intake has no relationship with stunting, and family income levels have no relationship with stunting. There is a relationship between iron intake and the incidence of stunting while the intake of energy, protein, vitamin A and the level of family income have no relationship with the incidence of stunting.